Analisis Kemampuan Manajerial Kepala Sekolah Dalam Implementasi Pembelajaran Daring - Afif Tri Hastowo; Muhammad Abduh (Program Studi Pendidikan Guru Sekolah Dasar, Universitas Kristen Satya Wacana, 2021)
The Covid-19 pandemic has a major impact, especially on education in elementary schools, so that the managerial skills of school principals are needed in implementing online learning in schools. This study aims to describe the form of principal managerial abilities and to describe the obstacles faced by the principal and the solutions made by the principal in overcoming problems. This research uses descriptive qualitative research. The data collection methods used were interviews and documentation. The results of this study indicate that the principal managerial ability, seen from the aspects of planning, organizing, activating, and monitoring, has been carried out quite well with special steps taken by the principal. The obstacles faced by the principal come from two factors, namely internal constraints in the form of limited ICT skills of teachers and a lack of learning innovation, as well as external constraints due to limited facilities and infrastructure used by students. The solution made by the principal in internal problems is in the form of guidance and direction to the teacher and efforts to increase the ability of teachers through training, while for external problems, namely by maximizing facilities and infrastructure, forming student study groups and conducting home visits.